(untitled) (AYUSHDHARA, 2025)
Ischemic heart disease (IHD) causes large number of mortalities, a significant public health concern, responsible for approx. 1.7 million deaths annually accounting about 15.2% of all death due to stressful fast, Sedentary life style, unhealthy food. Objective: to assess the efficacy of Nitya anulomana, Hridabasti and Hridya rasayana prayoga in spectrum of IHD. Methodology: Prospective randomised, open labelled modern controlled add on clinical experimental study. Diagnosed cases of IHD were treated with Nitya Anulomana by administering Haritakyadi churna 3gm before food with warm water daily night. Hridbasti with Bilwadi tailam 30 min for 7 days and again for 7 days after giving 7 days gap and Chatushparni rasayana was orally administered 500mg 2 capsules twice a day before food for 48 days, Prabhakara vati 1 tab before food bd for 48 days and Bilwadi Kashaya 15ml with 15ml of water BD as Anupana as add on therapy. Result: intervention showed improvement in subjective parameters like Hritashoola, Arohana ayasa, Hritagouravata, etc and objective like ejection fraction, lipid profile, blood pressure, ECG and 2d echo. Conclusion: IHD is result from atherosclerosis plaque accumulation and subsequent narrowing of the arterial lumen. reduced ejection fraction can be improved with Ayurvedic intervention, with Nitya anulomana by administering Haritakyadi churna. Hridbasti with Bilwadi tailam chatushparni hridya rasayana, Prabhakara vati and Bilwadi Kashaya as add on therapy.